The Cartagena Protocol on Biosafety: A comparative analysis of the domestic implementation in South Africa and Uganda - Mutesasira, Peter Davis (Institute of Marine and Environmental Law, 2014)
This study makes a comparative analysis of the current biosafety legislation in South Africa and the interim biosafety regulatory regime in Uganda. A set of common characteristics and components in biosafety regulatory systems with reference to related provisions of the Cartagena Protocol on Biosafety were used. The introduction of genetically modified organisms (GMOs) especially in agriculture has produced a new range of governance challenges in the fields of environmental safety and human health. The regulation of modern biotechnology in Africa is still in its infancy. Despite this, legislation is urgently required to regulate modern biotechnology. The study assessed how the Cartagena Protocol on Biosafety is implemented by South Africa and Uganda. The study revealed that though the Cartagena Protocol has gone some way in regulating modern biotechnology, its implementation in countries such as South Africa and Uganda has not resulted in the harmonization of the domestic regulatory process. On the national level, the study noted that the biosafety legislation of South Africa and the interim biosafety regulatory regime of Uganda do not fully comply with the provisions of the Cartagena Protocol. This is mainly because each country has taken a different approach in implementing the protocol depending on its domestic priorities, imperatives and position in the global agricultural market. Finally, the study made recommendations on possible ways in which South Africa and Uganda can coordinate and harmonize their national biosafety regulatory systems. These will enable the two biosafety regulatory systems to become more compliant with the provisions of the protocol.